Causal Factors Influencing the Success of Health Spa Business in Thailand - Sojiphlakul, Saranthon (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aims (1) to analyze the factors influencing the success of the health spa business in Thailand and (2) to examine the coherence of the causal relationship model of the factors influencing business success of health spas in Thailand with the empirical data. This research used mixed method research. The quantitative research method was collecting data by using questionnaires from health spa business entrepreneurs. The population was 9,080 and the sample size was 400 people. The qualitative research method was using in-depth, semi-structured interviews from 15 key informants related to health spa business. The statistics used in the data analysis were percentage, mean, and standard deviation. Data analysis to test research hypothesis was based on structural equation analysis. The results showed that (1) The causal factors that had the most direct influence on the success of a health spa business were focus on service followed by the focus on marketing and service innovation respectively, the three variables could explain the variance in the success of the health spa business (R2) equal to 0.87 (87.0%) and (2) the causal relationship model found that the correlation model according to the research concept was consistent with the empirical data. The harmonious index of the model was as follows: X2=288.85, df=116, X2 / df = 1.973, p-value = 0.051, GFI = 0.955, AGFI = 0.953, CFI = 0.988, NFI = 0.976, TLI = 0.988, RMSEA = 0.049. Article history: Received 1 May 2022 Revised 21 May 2022 Accepted 23 May 2022 SIMILARITY INDEX = 3.69 %